Adenosine receptor A1 regulates polymorphonuclear cell trafficking and microvascular permeability in lipopolysaccharide-induced lung injury - Ngamsri, Kristian-Christos; Wagner, Rosalyn; Vollmer, Irene; Stark, Stefanie; Reutershan, Joerg (Journal of Immunology, 2010)
Extracellular adenosine and adenosine receptors are critically involved in various inflammatory pathways. Adenosine receptor A1 (A1AR) has been implicated in mediating transmigration of leukocytes to sites of inflammation. This study was designed to characterize the role of A1AR in a murine model of LPS-induced lung injury. LPS-induced transmigration of polymorphonuclear cells (PMNs) and microvascular permeability was elevated in A1AR-/- mice. Pretreatment of wild-type mice with the specific A1AR agonist 29Me-2-chloro-N6- cyclopentyladenosine attenuated PMN accumulation in the interstitium and alveolar space as well as microvascular permeability. Lower PMN counts in the lungs of pretreated wild-type mice were associated with reduced amounts of the chemotactic cytokines TNF-α, IL-6, and CXCL2/3 in the bronchoalveolar lavage. Pretreatment was only effective when A1AR was expressed on hematopoietic cells as demonstrated in chimeric mice. These findings were confirmed by in vitro transmigration assays demonstrating that chemokine-induced transmigration of PMNs was reduced when PMNs but not when pulmonary endothelial or alveolar epithelial cells were pretreated. 2′Me-2-chloro-N6-cyclopentyladenosine prevented pulmonary endothelial but not epithelial cells from LPS-induced cellular remodeling and cell retraction. Our data reveal what we believe to be a previously unrecognized distinct role of A1AR for PMN trafficking and endothelial integrity in a model of acute lung injury. Copyright © 2010 by The American Association of Immunologists, Inc.
CRIS-Team Scopus Importer:2022-11-17